2012
DOI: 10.1242/jeb.064717
|View full text |Cite
|
Sign up to set email alerts
|

Vocal tract articulation revisited: the case of the monk parakeet

Abstract: SUMMARYBirdsong and human speech share many features with respect to vocal learning and development. However, the vocal production mechanisms have long been considered to be distinct. The vocal organ of songbirds is more complex than the human larynx, leading to the hypothesis that vocal variation in birdsong originates mainly at the sound source, while in humans it is primarily due to vocal tract filtering. However, several recent studies have indicated the importance of vocal tract articulators such as the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
(43 reference statements)
0
20
1
1
Order By: Relevance
“…Short-duration calls are consistent with the fact that air cavities and respiratory organs were likely still small and undergoing substantial growth during this period (Vleck and Bucher, 1998). High frequencies are synonymous with short wavelengths of sound and are predicted from the resonant properties of small vocal tracts (Podos, 1996;Brittan-Powell et al, 1997;Hoese et al, 2000;Suthers and Zollinger, 2004;Beckers et al, 2004;Bradbury and Vehrencamp, 2011;Ohms et al, 2012). Broadband noise has been…”
Section: Early Noisy Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Short-duration calls are consistent with the fact that air cavities and respiratory organs were likely still small and undergoing substantial growth during this period (Vleck and Bucher, 1998). High frequencies are synonymous with short wavelengths of sound and are predicted from the resonant properties of small vocal tracts (Podos, 1996;Brittan-Powell et al, 1997;Hoese et al, 2000;Suthers and Zollinger, 2004;Beckers et al, 2004;Bradbury and Vehrencamp, 2011;Ohms et al, 2012). Broadband noise has been…”
Section: Early Noisy Stagementioning
confidence: 99%
“…The latter characteristic suggests an advantage to calling while flapping. Because downstroke phases are often synchronized with expiratory phases (Tucker, 1968;Boggs, 1997;Tobalske and Dial, 1994), and vocal production requires a build-up of positive expiratory pressure at the sub-syringeal aperture (Suthers, 1997;Cooper and Goller, 2004;Ohms et al, 2012), contact call emission may be more economical during flapping phases and less so during non-flapping phases when inspiration is likely more economical. In support of this explanation, nestling call durations showed an abrupt decrease shortly after they began using wings to aid locomotor displacements inside the nest cavity.…”
Section: Reasons For Short Contact-call Durationsmentioning
confidence: 99%
“…A high-low placement of the tongue changes the frequency of the first formant, and a front-back placement changes the frequency of the second formant. Although little is known about their importance in avian communication, formants or harmonic-rich formant-like structures are also observed in the vocalizations of various bird species, including zebra finches (Ohms et al, 2010), mynah birds (Klatt and Stefanski, 1974), African gray parrots (Pepperberg, 2010) and monk parakeets (Beckers et al, 2004;Ohms et al, 2012). The ability of mynah birds and parrots to modify formants contributes to their ability to imitate human speech, although the production mechanism may not be identical to that found in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment in which the syrinx of a euthanized monk parakeet was replaced with a speaker, Beckers et al (2004) found that artificially manipulating front-back tongue placement caused changes in formant frequency and amplitude, and manipulating high-low placement caused changes in amplitude. Ohms et al (2012) used Xray cineradiography to measure tongue height in naturally vocalizing monk parakeets. Changes in tongue height were observed during the production of various natural call notes.…”
Section: Introductionmentioning
confidence: 99%
“…), in the open‐mouth vocalizing species monk parakeet ( Myiopsitta monachus ; Ohms et al. ), or in the open‐mouth vocalizations of songbirds (Riede and Suthers ; Ohms et al. ; Riede and Goller ; Riede et al.…”
Section: Morphological and Biomechanical Aspects Of Inflation Of The mentioning
confidence: 99%